Rapid Drink Challenge in high‐resolution manometry: an adjunctive test for detection of esophageal motility disorders. Issue 1 (15th July 2016) - Ang, D.; Hollenstein, M.; Misselwitz, B.; Knowles, K.; Wright, J.; Tucker, E.; Sweis, R.; Fox, M.
Abstract: Background/Aims: The Chicago Classification for diagnosis of esophageal motility disorders by high‐resolution manometry (HRM) is based on single water swallows (SWS). Emerging data suggest that a "Rapid Drink Challenge" (RDC) increases sensitivity for motility disorders. This study establishes normal values and diagnostic thresholds for RDC in clinical practice. Methods: Two cohort studies were performed in patients with dysphagia or reflux symptoms (development and validation sets). Healthy subjects and patient controls provided reference values. Ten SWS and two 200‐mL RDC were performed. Primary diagnosis for SWS was established by the Chicago Classification. Abnormal RDC was defined by impaired esophagogastric junction (EGJ) function (elevated integrated relaxation pressure during RDC [IRP‐RDC]); incomplete inhibition of contractility during and ineffective contraction after RDC. Diagnostic thresholds identified in the development set were prospectively tested in the validation set. Results: Normal values were determined in healthy (n=95; age 37.8 ± 12) and patient controls (n=44; age 46.4 ± 15). Development and validation sets included 178 (54 ± 17 years) and 226 (53 ± 16 years) patients, respectively. Integrated relaxation pressure during RDC was higher for SWS than RDC in all groups (overall P <.001), except achalasia. Rapid Drink Challenge suppressed contractility, except in achalasia type III, spasm, and hypercontractile motility disorders ( P <.001). An effective after‐contraction was present more often in health than disease ( P <.001). Optimal diagnostic thresholds identified in the development set (IRP‐RDC ≥12 mmHg achalasia, IRP‐RDC ≥ 8mmHg "all cause" EGJ dysfunction), were confirmed in the validation set (both, sensitivity 85%, specificity >95%). Conclusions: Rapid Drink Challenge contributes clinically relevant information to routine HRM studies, especially in patients with EGJ dysfunction. Abstract : Emerging data suggest that a 200‐mL Rapid Drink Challenge (RDC) test provides additional information during esophageal high‐resolution manometry (HRM). We present normal values for RDC from healthy volunteers and patient controls and establish diagnostic thresholds for esophagogastric junction (EGJ) and peristaltic dysfunction. Rapid Drink Challenge is simple to perform during routine HRM studies and appears to increase diagnostic yield for symptomatic EGJ outflow obstruction and other, clinically relevant, motility disorders.